WMIP Model, A Resolution for Traditional Madrasah Teaching and Operation Implementation in Davao Region - Saprolla Rollie Cale Deporos; Aan Komariah; Dedy Achmad Kurniady (EARR (Educational Administration Research and Review), 2022)
This research aims to propose the WMIP Model or Weekend Madrasah Implementation Program as an alternative resolution for the development of Traditional Madrasah Teaching and Operation in Davao Region, Philippines. The qualitative method is used based on the interview results through madrasah education experts and implementors in the said region, other related studies results, related provisions, and laws aligned to Madrasah program in the Philippines are the instruments used in reaching the result. The vital points of this study are; to enhance the pedagogical skills of the teachers (asatidhs) and develop the partnership of government schools and weekend madrasah towards the unity in education as DepEd’s vision, to support the development of the country as a whole.